Prediagnostic circulating markers of inflammation and risk of oesophageal adenocarcinoma: a study within the National Cancer Institute Cohort Consortium. Issue 6 (18th August 2018) - Cook, Michael B; Barnett, Matthew J; Bock, Cathryn H; Cross, Amanda J; Goodman, Phyllis J; Goodman, Gary E; Haiman, Christopher A; Khaw, Kay-Tee; McCullough, Marjorie L; Newton, Christine C; Boutron-Ruault, Marie-Christine; Lund, Eiliv; et al.
Abstract : Objective: Cross-sectional data indicate that systemic inflammation is important in oesophageal adenocarcinoma. We conducted a prospective study to assess whether prediagnostic circulating markers of inflammation were associated with oesophageal adenocarcinoma and to what extent they mediated associations of obesity and cigarette smoking with cancer risk. Design: This nested case–control study included 296 oesophageal adenocarcinoma cases and 296 incidence density matched controls from seven prospective cohort studies. We quantitated 69 circulating inflammation markers using Luminex-based multiplex assays. Conditional logistic regression models estimated associations between inflammation markers and oesophageal adenocarcinoma, as well as direct and indirect effects of obesity and smoking on risk of malignancy. Results: Soluble tumour necrosis factor receptor 2 (sTNFR2) (ORsquartile 4 vs 1 =2.67, 95% CI 1.52 to 4.68) was significantly associated with oesophageal adenocarcinoma. Additional markers close to the adjusted significance threshold included C reactive protein, serum amyloid A, lipocalin-2, resistin, interleukin (IL) 3, IL17A, soluble IL-6 receptor and soluble vascular endothelial growth factor receptor 3. Adjustment for body mass index, waist circumference or smoking status slightly attenuated biomarker–cancer associations. Mediation analysis indicated that sTNFR2 may account for 33% (p=0.005) of the effect of waist circumference on oesophageal adenocarcinoma risk. Resistin, plasminogen activator inhibitor 1, C reactive protein and serum amyloid A were also identified as potential mediators of obesity–oesophageal adenocarcinoma associations. For smoking status, only plasminogen activator inhibitor 1 was a nominally statistically significant (p<0.05) mediator of cancer risk. Conclusion: This prospective study provides evidence of a link between systemic inflammation and oesophageal adenocarcinoma risk. In addition, this study provides the first evidence that indirect effects of excess adiposity and cigarette smoking, via systemic inflammation, increase the risk of oesophageal adenocarcinoma.